Usefulness factors to predict the continuance intention using mobile payment, case study: GO-Pay, OVO, Dana - Lateefa, Cholilah; Naufalia, Ryanis; Yassar, Danendra (SHM Publisher, 2021)
The advancement of information technology continues to grow in line with the increasing years. The benefits gained from the advancement of information technology make all aspects of human life today can not be separated from information technology and also ikut encouragethe emergence ofinnovations in thedevelopment of informationtechnology, sepertinya payment is no longer conventionally nal but with mobile payment. This study aims to find out what useful factors influence the continuation of the intention to use mobile payment in the go-pay, OVO, and DANA case studies. Analysis of factors that influenced this study include: Computer Self Efficacy (CSE), Enjoyment (E), Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Confirmation (CON), Perceived Value (PV), Technical System Quality (TSQ), Satisfaction (SAT),and Continuance Intention (CI). This study uses random sampling techniques by collecting data utilizing google form containing 45 statements using five Likert-scale distributed online. The sample used in this study was 117 respondents. The statistical analysis techniques used in this study are Structural Equation Modeling (SEM) and use SMARTPLS 3.0 application as a tool to analyze the data. The results obtained are that Computer-Self Efficacy (CSE), Perceived Ease of Use (PEOU), and Perceived Usefulness (PU) has no significant effect on Continuance Intention (CI). While Satisfaction (SAT), has a significant influence on Continuance Intention (CI).